New Efficient Synthesis of 2,3,5-Trisubstituted Pyrimidin-4(3H)-ones from Baylis–Hillman Adducts - Zhong, Ying; Wu, Lei; Ding, Ming-Wu (Synthesis, 2012)
Azides obtained from Baylis–Hillman adducts were treated with triphenylphosphine to give the corresponding iminophosphoranes that underwent aza-Wittig reactions with aryl isocyanates and then reacted with amines, alcohol, or phenols in the presence of catalytic amounts of sodium alkoxide or potassium carbonate to give the corresponding 2,3,5-trisubstituted pyrimidin-4(3H)-ones directly in good yields.
Keywords: azides; heterocycles; cyclizations; Wittig reactions; amines; alcohols; phenols